Impact of Zoysiagrass and Tall Fescue Seed Mixtures on Brown Patch Severity - Mingying Xiang; J. Fry; M. Kennelly (Kansas Agricultural Experiment Station Research Reports, 2017)
Earlier research has demonstrated that polystands of zoysiagrass and tall fescue can be established successfully, with the potential to provide a high-quality turfgrass stand with reduced inputs. Our objective was to determine whether mixing zoysiagrass with tall fescue will reduce brown patch severity while maintaining overall acceptable quality. Studies were established at the Rocky Ford Turfgrass Research Center in Manhattan, KS. In the split-plot design, natural infection byRhizoctonia solanior a fungicide-treated control was the whole-plot treatment factor and species (tall fescue monostand and the zoysiagrass/tall fescue mixture) were subplots. During July and August 2016, when hot, humid weather triggers brown patch, excessive irrigation was applied to promote brown patch. Disease severity was measured by visual ratings and digital image analysis; number of infected leaves in each plot was recorded using a grid. The mixed stand then showed less plot area affected by brown patch disease compared to the monostand of tall fescue.
Keywords: Disease; turfgrass